(untitled) (Journal of Family Sciences, 2023)
Adapting to a new situation is not easy thing to do, especially if the situation you face is very different from the previous situation. This study aimed to determine the relationship between self-adjustment and the psychological well-being of students at Asshiddiqiyah 2 Islamic Boarding School, Tangerang, Banten. Data were collected in May 2022, using a correlational approach. The population in this study was students aged 13-16 years with a total sample of 130 male and female respondents. The sample in this study was determined using proportional stratified random sampling with data collection techniques using a questionnaire (questionnaire) adjustment and psychological well-being. Spearman’s rank correlation coefficient was used to test the data hypothesis. The results of the analysis show that the correlation coefficient between self-adjustment and psychological well-being is 0.989, with t count 7.078 > t table 1.960. It can be concluded that there is a significant relationship between self-adjustment and the psychological well-being of students at Asshiddiqiyah 2 Islamic Boarding School, Tangerang Banten. The theoretical implication of this study is that self-adjustment and psychological well-being have a positive relationship. Based on the analysis results, the relationship between self-adjustment and psychological well-being was strong and significant.